Optimization of Functional Diagnostics of Gastrointestinal Tract Diseases (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article provides a literary analysis of current trends in the functional diagnosis of diseases of the gastrointestinal tract. For this purpose, foreign and domestic scientific articles and scientific research results were analyzed.